Fed-batch versus batch cultures of Yarrowia lipolytica for γ-decalactone production from methyl ricinoleate - Gomes, Nelma (2012)
Constant medium feeding rate and intermittent fed-batch fermentation strategies were investigated aiming to increase the yields of γ-decalactone production by Yarrowia lipolytica, using methyl ricinoleate as substrate and ricinoleic acid source. The accumulation of another compound, 3-hydroxy-γ-decalactone, was also analyzed since it derives from the direct precursor of γ-decalactone thereby providing information about the enzymatic activities of the pathway. Both strategies were compared with the traditional batch mode in terms of overall productivity and yield in respect to the substrate. Although the productivity of γ-decalactone was considerably higher in the batch mode (168 mg l−1 h−1), substrate conversion to lactone (73 mg γ-decalactone g−1) was greater in the intermittent fed-batch giving 6.8 g γ-decalactone l−1. This last strategy therefore has potential for γ-decalactone production at an industrial level.